Sistem Pembayaran Online Melalui Aggregator Menggunakan Restful Api dan Framework Laravel - Hanum, Gilang Kartika; Sari, Meri Mayang; Andwiyan, Denny (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2024)
The rapid development of technology causes the need for information systems to increase to encourage people to carry out an activity so that it can be carried out quickly and precisely, and are required to be able to make decisions using the right method. so as to obtain benefits for the progress of information systems. The information system needed in handling the payment process must be precise and fast, errors in the payment entry process and payment calculation and the process of recording payment results. Currently the handling of tuition payments is still done semi-computerized using Microsoft Excel. then a system is needed that can equalize or convert courses. The method used in this information system is the SDLC (System Development Life Cycle) method of the waterfall type model, which is expected to be able to easily determine the achievement of a system, where a website system that has been designed uses PHP with the Laravel Framework as its programming language and MySQL as a container. database storage, and UML (Unified Modeling Language) as a system model to describe the flow of procedures in the form of objects consisting of Use Case Diagrams, Activity Diagrams, and Sequence Diagrams, The results of this test are in the form of data or information about payments. From the test results, it can be concluded that this system can perform the expected functions. Hopefully with this system, it can help the finance department to check the results of student payments in order to know whether the payment results are correct or not, so as to minimize recalculation in the management of financial statements.